Koszt witryny internetowej - Ziętowska, Irena (Cost of the Website, 2006)
More and more companies design their own websites for both external and internal users and incur many different elements of costs. From the point of view of accounting one needs to solve some problems concerning the appropriate bookkeeping approach to these costs. The paper describes the issues concerning the presentation of the costs of website as a element of intangible assets according to International Accounting Standard IAS 38 and its interpretation SKI 38.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 425-431